ASSESSING CONTAMINATION LEVEL OF JAKARTA BAY NEARSHORE SEDIMENTS USING GREEN MUSSEL (PERNA VIRIDIS) LARVAE - Cordova, Muhammad Reza; Purbonegoro, Triyoni; Puspitasari, Rachma; Hindarti, Dwi (Marine Research in Indonesia, 2016)
Indication of accumulation of heavy metal in sediments will lead to problem for shore and sea ecosystems, biota living in that area and humanâs health. The research is aiming to analyse the toxicity of sediment from thirty one locations in Jakarta Bay using Perna Viridis. High amount in larval abnormality found in sediments from the area near mainland and estuary are an indication of high influence of waste from anthropogenic activities from Jakarta mainland. These areas are down stream of Cengkareng Drain, Kamal River, Grogol River and Cakung River, area around sea transportation and North Jakarta Integrated Industrial Area. Sediment of Jakarta Bay, especially coming from estuary area and near to the land area causes an increase in green mussel larval abnormality. This indicates the high of waste influence from anthropogenic activity from Jakarta land area.